ChemInform Abstract: Enantioselective Cycloaddition of Carbonyl Ylides with Arylallenes Using Rh2(S‐TCPTTL)4. Issue 50 (10th December 2013) - Krishnamurthi, Janagiraman; Nambu, Hisanori; Takeda, Koji; Anada, Masahiro; Yamano, Akihito; Hashimoto, Shunichi
Abstract The first catalytic asymmetric cycloaddition of carbonyl ylides, derived from diazoketoesters (I), with arylallenes (II) proceeds in a fully chemo‐ and regioselective manner to give 8‐oxabicyclo[3.2.1]octanes (III) (18 examples) with excellent enantio‐ and exo‐diastereoselectivity.